PHARMACOEPIDEMIOLOGY OF ORIGINAL DROTAVERINE USE IN DYSMENORRHEA: RESULTS OF AN INTERNATIONAL MULTICENTER STUDY - A. L. Unanyan; V. A. Alimov; S. E. Arakelov; M. S. Afanasyev; D. V. Baburin; D. V. Blinov; T. D. Guriyev; U. V. Zimovina; A. E. Kadyrova; Yu. M. Kossovich; L. S. Polonskaya (Фармакоэкономика)
spasmodic abdominal pain is a common complaint. Dysmenorrhea is one of the most important problems not only from medical, but also social point of view. Drotaverine hydrochloride is a potent smooth muscle spasmolytic agent. Objective: To evaluate the effectiveness of drotaverine in the daily practice management of spasmodic abdominal pain due to gastrointestinal, biliary, urological tract conditions and dysmenorrhea. Material and Methods: a multicenter, prospective, cross-sectional and longitudinal product registry (3 visits), non-interventional on the therapeutic strategy was conducted in Mexico, Kazakhstan, and Russia. Each investigator contributed at the 2 sequences: one cross-sectional, assessing physicians' interest for and knowledge of spasmodic abdominal pain management [Prescription Registry, PR] and longitudinal registry [LREG]: data on 25 consecutive eligible patients with spasmodic pain were recorded in the PR, and 5-day (+3) follow-up on the first 5 consecutive eligible patients receiving NOSPA ® . Pain was evaluated asking patients to rate the worst abdominal pain over the past 12 hours (11-point Numerical Pain Rating Scale, NPRS) and a Visual Analogue Scale (VAS) to evaluate the drotaverine onset of action. Only spontaneous adverse events reports were collected. Results: 208 physicians participated and included 5507 patients. 75% of them received drotaverine. Treatment was mostly prescribed in monotherapy (72%). From these patients, 1116 were included in the Longitudinal Registry (881 in the PP population) with a mean age of 34.2 ± 12.5 years. 86 % were females. Most suffered from dysmenorrhea (53%). They received drotaverine for 5.7±4 days. 89% were responders. Compared to the first evaluation, a statistical difference was observed in patients suffering from dysmenorrhea (p<0.0001). Conclusion: Results show that pain rapidly improves in patients suffering from spasmodic abdo minal pain when taking drotaverine in this open product registry conducted under conditions of real life. It is possible to discuss introduction of drotaverine in national guidelines for management of dysmenorrhea patients.